2022
DOI: 10.1111/pai.13732
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in cord blood in relation to prenatal traffic‐related air pollution: The NELA cohort

Abstract: and Fondos FEDER. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(112 reference statements)
1
7
0
Order By: Relevance
“…Weng et al showed that abnormal mitochondrial respiratory chain metabolism also leads to impairment of invariant natural killer T cell (iNKT) preactivation and reduced T cell receptor (TCR) signaling ( 33 ). This is consistent with the reports of neonatal immune deficiency due to air pollution exposure ( 34 ). The current study demonstrated that Uqcrfs1 protein expression was diminished after environmental exposure to waterfall forest aerosols, further weakening the electron transport activity.…”
Section: Discussionsupporting
confidence: 93%
“…Weng et al showed that abnormal mitochondrial respiratory chain metabolism also leads to impairment of invariant natural killer T cell (iNKT) preactivation and reduced T cell receptor (TCR) signaling ( 33 ). This is consistent with the reports of neonatal immune deficiency due to air pollution exposure ( 34 ). The current study demonstrated that Uqcrfs1 protein expression was diminished after environmental exposure to waterfall forest aerosols, further weakening the electron transport activity.…”
Section: Discussionsupporting
confidence: 93%
“…Although statistically not significant, the recent epidemiological study from García-Serna et al 5 found that odds of detectable concentration of IL-17F tended to be decreased in the cord blood of infants exposed to higher air pollution during the pregnancy. Thus, the mouse model data, 3 our data from human infants as well as data from García-Serna et al 5 potentially reflect a suppressive effect on IL-17a levels during mouse and human immune system development, respectively. We speculate that not all life stages are equally influenced and some life stages, such as the perinatal period, are more susceptible due to the immaturity of the immune system.…”
Section: E T T E R T O T H E E D I T O R Ambient Prenatal Air Polluti...mentioning
confidence: 81%
“…On the basis of the prior knowledge obtained from previous scientific literature, additional covariates were further selected for statistical analysis . Ultimately, maternal age, education level, passive smoking, income, gestational age at delivery, BMI before pregnancy, and parity were included in the models as final covariates.…”
Section: Discussionmentioning
confidence: 99%